2019
DOI: 10.3390/ijerph16060972
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fitness and Quality of Life among Women over 60 Years of Age Depending on Their Level of Objectively Measured Physical Activity

Abstract: The aim of this study was to identify the differences in functional fitness and quality of life among women over 60 years of age depending on their level of objectively measured physical activity (PA) according to Global Recommendations on Physical Activity for health. The study used a cross-sectional design with 213 female volunteers over 60 years of age. Physical activity was monitored for 7 days of the week using an Actigraph Gt3X monitor. The Senior Fitness Test battery and hand-grip strength tests were pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…In our study, the HGS of the elderly with low PA was significantly lower than that of the elderly with high PA (22.95 (17.82, 31.00) vs. 27.05 (21.80, 33.73), P < 0.01) at baseline. This is consistent with previous reports that have shown that female volunteers over 60 years of age who did not meet the PA recommendations had low physical function [26]. Our finding that the HGS of elderly patients with CLD and low PA decreased significantly indicated that decrease in physical function and PA affect each other.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the HGS of the elderly with low PA was significantly lower than that of the elderly with high PA (22.95 (17.82, 31.00) vs. 27.05 (21.80, 33.73), P < 0.01) at baseline. This is consistent with previous reports that have shown that female volunteers over 60 years of age who did not meet the PA recommendations had low physical function [26]. Our finding that the HGS of elderly patients with CLD and low PA decreased significantly indicated that decrease in physical function and PA affect each other.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that characteristics of low PA included more living alone and more sarcopenia than those of high PA in elderly patients. A previous study showed that the quality of life domain of social relationships is declining in the low PA population [26]. Our results partially explained the reality of the decline in the quality of life domain of social relationships.…”
Section: Discussionsupporting
confidence: 75%
“…They found that PA women had a slight improvement in QoL scores, regardless of the area as women who were underactive 35 . Many studies have seen the positive impact of PA on the QoL 35,36,37,38 . In his study, Vagetti et al 14 2015detect improvement in the ten domains of QoL connected with higher frequency moderate to vigorous PA even at a weekly physical activity 14 .…”
Section: Discussionmentioning
confidence: 97%
“…The Nawrocka et al 35 (2019) study found that the QoL in the domain of social relationships is significantly related to the level of PA. They found that PA women had a slight improvement in QoL scores, regardless of the area as women who were underactive 35 . Many studies have seen the positive impact of PA on the QoL 35,36,37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation